Time for Growth - Battista Severgnini; Lars Boerner (Copenhagen Business School (CBS), Department of Economics, 2019)
This paper studies the impact of the early adoption of one of the most important high-technology machines in history, the public mechanical clock, on long-run growth in Europe. We avoid endogeneity by considering the relationship between the adoption of clocks with an instrument based on the appearance of repeated solar eclipses. This is motivated by the predecessor technologies of mechanical clocks, astronomic instruments that measured the course of heavenly bodies. We find a significant increase in growth rates between 1500 and 1700 in the range of 30 percentage points in early adopter cities and areas. Finally, additional quantitative analysis suggests a positive relationship between mechanical clocks and contemporary long-term orientation nowadays.
hdl:10398/9730
Keywords: N13; N93; O33; 330; technological adoption; cities; mechanical clocks; information technology; long-term orientation